2019
DOI: 10.24002/kinerja.v23i1.2123
|View full text |Cite
|
Sign up to set email alerts
|

Halal Marketing and Financial Performance: Study in Cosmetic Companies in Indonesia

Abstract: This study aims to prove the empirically relationship between halal marketing (halal labelling and hijabista celebrity endorsement) with financial performance. The independent variable is halal labeling and hijabista celebrity endorse, while the dependent variable is financial performance. This research was conducted in Indonesia, spread across five cities such as: Jakarta, Lampung, Bali, West Sulawesi, and Aceh with samples of PT. Paragon Technology and Innovation and PT. Sari Ayu., Tbk. Survey methods and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Muslim women today are more conscious about their self-image and social identity when it comes to fashion choice. Recently, Muslim women actively assert their visible Muslim identity in the public sphere through their fashion choice (Pratisti and Maryati, 2019; Williams and Kamaludeen, 2017). Fashion consciousness is one of the most important factors influencing consumer purchasing decisions, particularly when it comes to clothing (Hassan and Harun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Muslim women today are more conscious about their self-image and social identity when it comes to fashion choice. Recently, Muslim women actively assert their visible Muslim identity in the public sphere through their fashion choice (Pratisti and Maryati, 2019; Williams and Kamaludeen, 2017). Fashion consciousness is one of the most important factors influencing consumer purchasing decisions, particularly when it comes to clothing (Hassan and Harun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nordin et al (2016) stated that halal certificate would improve the company's financial performance as the certification process requires the most ultimate level of quality standards. Conversely, findings of Pratisti and Maryati (2019) found that halal certification for the commercial industry did not have a significant impact on financial performance. In line with the study, Yunos et al (2014) stated that although the halal label increases consumer confidence, its effect on the company's financial performance remains unknown.…”
Section: Introductionmentioning
confidence: 85%